How sequential reduction of terminal electron acceptors modulates nitrification and dynamics of nitrifying bacteria and archaea in a tropical vertisol. (10th April 2018) - Mohanty, Santosh Ranjan; Yadav, Rakhi; Dubey, Garima; Ahirwar, Usha; Ahirwar, Neha; Aparna, K.; Rao, D. L. N.; Kollah, Bharati
Abstract: Nitrification potential of a tropical vertisol saturated with water was estimated during sequential reduction of nitrate (NO3 − ), ferric iron (Fe 3+ ), sulphate (SO4 2− ) and carbon dioxide (CO2 ) in terminal electron-accepting processes (TEAPs). In general, the TEAPs enhanced potential nitrification rate (PNR) of the soil. Nitrification was highest at Fe 3+ reduction followed by SO4 2− reduction, NO3 − reduction and lowest in unreduced control soil. Predicted PNR correlated significantly with the observed PNR. Electron donor Fe 2+ stimulated PNR, while S 2− inhibited it significantly. Terminal-restriction fragment length polymorphism targeting the amoA gene of ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) highlighted population dynamics during the sequential reduction of terminal electron acceptors. Only the relative abundance of AOA varied significantly during the course of soil reduction. Relative abundance of AOB correlated with NO3 − and Fe 2+ . Linear regression models predicted PNR from the values of NO3 −, Fe 2+ and relative abundance of AOA. Principal component analysis of PNR during different reducing conditions explained 72.90% variance by PC1 and 19.52% variance by PC2. Results revealed that AOA might have a significant role in nitrification during reducing conditions in the tropical flooded ecosystem of a vertisol.